2015
DOI: 10.1128/aem.03973-14
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Solvent Stress Cross-Tolerance Conferred to Corynebacterium glutamicum by Adaptive Laboratory Evolution

Abstract: bReinforcing microbial thermotolerance is a strategy to enable fermentation with flexible temperature settings and thereby to save cooling costs. Here, we report on adaptive laboratory evolution (ALE) of the amino acid-producing bacterium Corynebacterium glutamicum under thermal stress. After 65 days of serial passage of the transgenic strain GLY3, in which the glycolytic pathway is optimized for alanine production under oxygen deprivation, three strains adapted to supraoptimal temperatures were isolated, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 69 publications
0
52
0
Order By: Relevance
“…In an economically optimized bioprocess, microorganisms should be able to grow on low‐purity feedstock (lower substrate costs) and at favorable process conditions (e.g., at a higher temperature, to reduce cooling costs). An improved heat tolerance was reported for C. glutamicum after a repetitive batch ALE (rbALE) of 65 days, in which the temperature was gradually increased from 38 °C to 41.5 °C . Sequencing of three evolved isolates revealed a surprisingly high amount of 295 point mutations and two genomic deletions in total.…”
Section: Improving Performance Under Industrial Conditionsmentioning
confidence: 94%
See 1 more Smart Citation
“…In an economically optimized bioprocess, microorganisms should be able to grow on low‐purity feedstock (lower substrate costs) and at favorable process conditions (e.g., at a higher temperature, to reduce cooling costs). An improved heat tolerance was reported for C. glutamicum after a repetitive batch ALE (rbALE) of 65 days, in which the temperature was gradually increased from 38 °C to 41.5 °C . Sequencing of three evolved isolates revealed a surprisingly high amount of 295 point mutations and two genomic deletions in total.…”
Section: Improving Performance Under Industrial Conditionsmentioning
confidence: 94%
“…Interestingly, both the reverse engineered strain and the evolved strain lost the ability to grow on ethanol. This showed that, in contrast to an observed beneficial cross‐tolerance for isobutanol after ALE for increased temperatures, a single‐target ALE approach is typically associated with significant negative trade‐off effects.…”
Section: Improving Performance Under Industrial Conditionsmentioning
confidence: 99%
“…E. coli strains were grown at 37°C in LB medium [49]. Growth at high temperatures was evaluated as described previously [9]. Growth at high temperatures was evaluated as described previously [9].…”
Section: Methodsmentioning
confidence: 99%
“…Here, industrial strain development strongly benefits from adaptive evolution approaches, in which strains typically feature only a few mutations and which enable the enrichment of nonintuitive beneficial mutations by improving growth at the same time (Abatemarco et al, 2013;Portnoy et al, 2011). Up to now, laboratory evolution experiments of mainly fitness-linked phenotypes have been performed by exposing microorganisms to sequentially increasing levels of environmental stress (Eckdahl et al, 2015;Lee et al, 2013;Marietou et al, 2014;Oide et al, 2015;Reyes et al, 2014). Especially in the case of the yeast Saccharomyces cerevisiae, adaptation to an improved ethanol tolerance has been proven useful for increasing product formation (Alper et al, The bottom line of almost all reported adaptive evolution approaches is selection for improved growth and survival, which usually coincides with increased product formation -especially in the case of growth-coupled processes (Feist et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Short generation times and a natural mutation frequency of 10 À 10 to 10 À 9 mutations per base pair per replication cycle enable the selection of beneficial phenotypical traits from high genetic diversity (Barrick and Lenski, 2013). During the last few years, laboratory evolution strategies went more and more into the focus to adapt industrial producer strains to detrimental growth conditions such as oxidative and thermal stress (Lee et al, 2013;Oide et al, 2015;Sandberg et al, 2014;Tenaillon et al, 2012), to improve product formation (Raman et al, 2014;Reyes et al, 2014;Xie et al, 2015) or solvent tolerance (Atsumi et al, 2010;Lee et al, 2011;Oide et al, 2015) (for reviews discussing the use of adaptive evolution approaches in metabolic engineering, see Abatemarco et al, 2013;Portnoy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%